Logical conditions analysis method for diagnostic test results decoding applied to competence elements proficiency - Freyman, V.I. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2015)
Subject of Research.Representation features of education results for competence-based educational programs are analyzed. Solution importance of decoding and proficiency estimation for elements and components of discipline parts of competences is shown. The purpose and objectives of research are formulated. Methods. The paper deals with methods of mathematical logic, Boolean algebra, and parametrical analysis of complex diagnostic test results, that controls proficiency of some discipline competence elements. Results. The method of logical conditions analysis is created. It will give the possibility to formulate logical conditions for proficiency determination of each discipline competence element, controlled by complex diagnostic test. Normalized test result is divided into noncrossing zones; a logical condition about controlled elements proficiency is formulated for each of them. Summarized characteristics for test result zones are imposed. An example of logical conditions forming for diagnostic test with preset features is provided. Practical Relevance. The proposed method of logical conditions analysis is applied in the decoding algorithm of proficiency test diagnosis for discipline competence elements. It will give the possibility to automate the search procedure for elements with insufficient proficiency, and is also usable for estimation of education results of a discipline or a component of competence-based educational program.